Integrasi Pendekatan Konstruktivisme dalam Model Problem Based Learning Berbasis Kooperatif untuk Meningkatkan Kompetensi Mahasiswa Pada Mata Kuliah Strategi Pembelajaran Biologi Tahun Akademik 2009/2010 - Bowo Sugiharto; Baskoro Adi Prayitno; Suciati Suciati (Bioedukasi: Jurnal Pendidikan Biologi, 2011)
ABSTRACT- This research aims to raise student competence trough the application of constructivism approach. A cooperative Problem Based Learning is used to achieve the aforesaid goal. This is a classroom action research that performed towards 48 university student at the fourth semester in Faculty of Teacher Training and Education. The          dependent variable in this research was student’s competence whereas the independent variable is the application of the aforementioned approach and model. By the application of Cooperative Problem Based Learning, the cognitive score has been raised and hence, its application towards is considered as effective.